Quantitative estimation of the state of vault feet gymnasts on the different stages of the long-term training - O.V. Makarova (Physical Education of Students, 2013)
The analysis of the vaults given about the state is conducted feet gymnasts on the different stages of the long-term training. 93 sportswomen of different qualification took part in research. The system of Big foot was used. It is set that on the early stages of the long-term training for gymnasts observed flattening heights of unevenness of navicular bone above the floor. With growth of qualification of sportswomen to avoid development of pathological changes of vaults feet actually not possibly. It is conditioned the rules of competitions to complication of competition compositions and technique of execution of elements of calisthenics. It is marked that appearance of flattening feet requires: corrections in the system of training; introduction of the specially developed methods on the removal of existent deformations; prophylaxis of flat-footedness; strengthening of musculoskeletal system feet.